The HVDC commutation failure mechanism impacted by harmonics and its suppression method - Zhang, Guojiang; Zhao, Jingbo; Jia, Yongyong; Zhou, Qian; Xu, Ke (Frontiers in Energy Research, 2024)
Harmonics are an important cause of voltage distortion, and voltage reduction and voltage distortion are the main causes of commutation failure. But most of the current research studies on commutation failure are based on the drop in fundamental voltage after a fault, and there are few reports on the impact of voltage distortion on commutation failure. Aiming to solve the above problem, this article first analyzes the generation and transmission characteristics of harmonics in AC and DC systems, as well as the coupling degree of harmonics in DC systems. Then, starting from the mechanism of the commutation process, a commutation failure analysis method based on the harmonic voltage time area is proposed. This method can quantitatively analyze the impact of different harmonics on commutation failure. On this basis, the harmonic criteria for causing commutation failure are established, and the harmonic characteristics of AC voltage when harmonics cause subsequent commutation failure are quantitatively analyzed. Finally, a preventive controller is proposed to suppress commutation failure caused by different harmonics, where the above analysis is verified by the simulations.